Perceptual bias and public programs : The case of the United States and hospital care - Meier, Kenneth J.; Johnson, Austin P.; An, Seung-Ho (Public Administration Review)
This article examines whether the public holds biased perceptions of public organizations (in this case, hospitals) in the United States and whether organizations get credit for positive results from program evaluations. Using an experimental design that replicates Hvidman and Andersen's 2016 Danish study, the study finds no negative public sector biases in the United States, but organizations are not given any credit for positive program evaluations. These results hold in two experimental replications. The implications of the findings for the measurement of public perceptions of government programs and for effective democratic governance are discussed. - Reproduced.
Keywords: Hospital care - United States